The Effectiveness of Monetary Policy and Imperfect Transmission Through The Banking Interest Rate Channel - Isman; Azhar Alam; Imron Rosyadi (Jurnal Iqtisad, 2026)
Monetary transmission has become increasingly constrained by transmission frictions and the non-linear relationship between the BI Rate and credit growth, reducing the effectiveness of monetary policy in the banking sector. Bank Indonesia’s 2025 Financial Stability Review indicates that the relationship between the BI Rate and credit growth is non-linear, challenging the assumptions of traditional monetary theory. Despite a relatively stable and accommodative policy rate, credit growth slowed considerably, declining from 12.36% (year-on-year) in June 2024 to 7.77% (year-on-year) in June 2025, indicating weaker banking intermediation. Although banking liquidity remained adequate, as reflected in 6.96% growth in Third-Party Funds (DPK), this did not translate into stronger credit expansion. Credit growth is projected to remain within the 8–11% range in 2025, suggesting that credit demand remains relatively unresponsive to monetary easing. These findings suggest the presence of transmission frictions, including banks’ risk-averse lending behaviour, weak credit demand, and structural constraints within the banking sector. This study aimed to analyse the effectiveness of monetary transmission using an explanatory sequential mixed-methods design that integrates quantitative and qualitative data analysis. The study examines whether reductions in the BI Rate stimulate credit growth or whether banking frictions constrain the effectiveness of monetary transmission. highlighting that the effectiveness of such policies depends on the behaviour of the banking sector, which serves as the main transmission channel. This study contributes to the literature by demonstrating that the effectiveness of monetary policy depends not only on policy rate adjustments but also on the banking sector’s role as the primary transmission channel.